2005
DOI: 10.1007/s11064-005-6771-1
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Glutathione S-transferase pi Expression in Central Nervous System of Subjects with Amyotrophic Lateral Sclerosis Using RNA Extraction from Formalin-Fixed, Paraffin-Embedded Material

Abstract: The expression of glutathione S-transferase pi (GST pi), an enzyme responsible for inactivation of a large variety of toxic compounds was studied in spinal cord, motor and sensory brain cortex obtained from patients who died in the course of amyotrophic lateral sclerosis (ALS). The studies were performed on formalin-fixed, paraffin-embedded (FFPE) and freshly frozen tissues. The method of RNA isolation from FFPE was modified. A significant decrease of GST pi-mRNA expression was found in cervical spinal cord an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Studies of GPx activities in erythrocyte samples from ALS patients have given mixed results with some showing significant diminution while others showed no change [165,166], analogous to the situation described for HD (above). Another study reported that mRNA levels for GST pi were significantly down regulated in the spinal cord, motor cortex, and the sensory cortex of ALS patients [114]. Furthermore a cohort of patients with a unique haplotype signature in the glutathione synthase gene was found to correlate with ALS patients who had exposures to metals and chemical solvents [167].…”
Section: Impairment Of Glutathione Homeostasis In Neurodegeneratimentioning
confidence: 99%
“…Studies of GPx activities in erythrocyte samples from ALS patients have given mixed results with some showing significant diminution while others showed no change [165,166], analogous to the situation described for HD (above). Another study reported that mRNA levels for GST pi were significantly down regulated in the spinal cord, motor cortex, and the sensory cortex of ALS patients [114]. Furthermore a cohort of patients with a unique haplotype signature in the glutathione synthase gene was found to correlate with ALS patients who had exposures to metals and chemical solvents [167].…”
Section: Impairment Of Glutathione Homeostasis In Neurodegeneratimentioning
confidence: 99%
“…These changes correlate with the disease progression. The spinal cord tissues obtained postmortem from patients with ALS showed increased protein glutathionylation in the gray matter [168] and reduced GST mRNA expression [169] compared to age-matched controls. Loss of GLT-1 has been reported in the spinal cord and motor cortex of ALS patients [170,171].…”
Section: Disorders Of Gsh Metabolism In Neurodegenerative Diseasementioning
confidence: 99%
“…Notably, impairment in defensive mechanisms has also been revealed in ALS, including downregulation of members of glutathione S-transferase family [54, 55], peroxiredoxins [56], and, in particular, the transcriptional factor Nrf2 [5760]. …”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%